Optimization for ultrasonic-microwave synergetic extraction of total iridoid glycosides and screening of analgesic and anti-inflammatory active fractions from patrinia scabra Bunge (Valerianaceae) - Quhuan Ma; Yanmei Lu; Yi Deng; Xiaodong Hu; Wanyu Li; Hongzhen Jia; Yuer Guo; Xiaofeng Shi (BMC, 2022)
Abstract Background Patrinia scabra Bunge is a well-known herbal medicine for its favorable treatment on inflammatory diseases owing to its effective ingredients, in which iridoid glycoside plays an extremely significant role. This article aimed to improve the content of total iridoid glycosides in crude extract through a series optimization of extraction procedure. Moreover, considering that both pain and inflammation are two correlated responses triggered in response to injury, irritants or pathogen, the article investigated the anti-inflammatory and analgesic activities of P. scabra to screen out the active fraction. Method P. scabra was extracted by ultrasonic-microwave synergistic extraction (UMSE) to obtain total iridoid glycosides (PSI), during which a series of conditions were investigated based on single-factor experiments. The extraction process was further optimized by a reliable statistical method of response surface methodology (RSM). The elution fractions of P. scabra extract were prepared by macroporous resin column chromatography. Through the various animal experiment including acetic acid-induced writhing test, formalin induced licking and flinching, carrageenan-induced mice paw oedema test and xylene-induced ear edema in mice, the active fractions with favorable analgesic and anti-inflammatory effect were reasonably screen out. Results The content of PSI could reach up to 81.42 ± 0.31 mg/g under the optimum conditions as follows: ethanol concentration of 52%, material-to-liquid ratio of 1:18 g/mL, microwave power at 610 W and extraction time of 45 min. After gradient elution by the macroporous resin, the content of PSI increased significantly. Compared with other concentrations of elution liquid, the content of PSI in 30 and 50% ethanol eluate was increased to reach 497.65 and 506.90 mg/g, respectively. Owing to the pharmacology experiment, it was reasonably revealed that 30 and 50% ethanol elution fractions of P. scabra could relieve pain centrally and peripherally, exhibiting good analgesic and anti-inflammatory activities. Conclusion Patrinia scabra possessed rich iridoids and exhibited significant analgesic and anti-inflammatory activities.